Cut, paste, kill [large type] : a Lomax & Biggs mystery - Karp, Marshall (Thorndike Press large print mystery, 2010)
When a socialite responsible for the death of a ten-year-old boy turns up murdered on the bathroom floor of a Hollywood hotel, Lomax and Biggs are confronted with a crime of artistic brutality. Along with the scissors sticking out of her lifeless body, they find a scrapbook documenting a motive for vengeance in lurid detail. As more bodies and scrapbooks are discovered, the hunt begins for a vigilante stalking unpunished criminals.